Handbook of Child Well-Being
142 illus., 76 illus. in color. eReference.
Keywords: The well-being of children represents a challenge not yet fully confronted and The Handbook of Child Well-being supplies its readers with a thorough overview of the complexities and implications regarding the scientific and practical pursuit of children's well-being. The handbook addresses the concept of well-being through an in-depth analysis of the perspectives and vocabularies of various disciplines such as, philosophy, theology, psychology and sociology. It covers important issues in child well-being and the problems of the general politics of well-being as well as the implementation of interventional programs and measures. In addition the handbook deals with the methods of measuring well-being for a scientifically grounded understanding and also for policy-making. The interdisciplinary set up of the handbook makes it a unique work that offers readers from a vast scope of child-related disciplines and professions a profound overview of the complexities and implications of thescientific and practical pursuit of children’s well-being.